2008
DOI: 10.1074/jbc.m800398200
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Triglyceride Transfer Protein Enhances Cellular Cholesteryl Esterification by Relieving Product Inhibition

Abstract: Cholesteryl ester synthesis by the acyl-CoA:cholesterol acyltransferase enzymes ACAT1 and ACAT2 is, in part, a cellular homeostatic mechanism to avoid toxicity associated with high free cholesterol levels. In hepatocytes and enterocytes, cholesteryl esters are secreted as part of apoB lipoproteins, the assembly of which is critically dependent on microsomal triglyceride transfer protein (MTP). Conditional genetic ablation of MTP reduces cholesteryl esters and enhances free cholesterol in the liver and intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 70 publications
4
30
3
Order By: Relevance
“…E: The bar graph of relative Abcg8 abundance (mean ± SE of 4 mice per group) after normalizing expression to Mttp f/f mice (n = 4 per group). * P < 0.05. ester, which was consistent with a role for Mttp in relieving product inhibition of cholesterol esterifi cation by transferring neutral lipid ( 28 ). Our fi ndings are consistent with that report and show that hepatic cholesterol ester content decreases in Mttp-LKO and DKO mice following LD feeding ( Tables 1-4 ).…”
Section: Discussionsupporting
confidence: 81%
“…E: The bar graph of relative Abcg8 abundance (mean ± SE of 4 mice per group) after normalizing expression to Mttp f/f mice (n = 4 per group). * P < 0.05. ester, which was consistent with a role for Mttp in relieving product inhibition of cholesterol esterifi cation by transferring neutral lipid ( 28 ). Our fi ndings are consistent with that report and show that hepatic cholesterol ester content decreases in Mttp-LKO and DKO mice following LD feeding ( Tables 1-4 ).…”
Section: Discussionsupporting
confidence: 81%
“…1D). Increased hepatic triglyceride and free cholesterol is consistent with previous studies (17,20). Increases in hepatic free cholesterol after MTP inhibition occur as accumulation of cholesterol ester inhibits their synthesis and enhances cellular free cholesterol accumulation (20).…”
Section: Increases In Hepatic-free Cholesterol Are Associated With Elsupporting
confidence: 80%
“…We previously reported that hepatic MTP deficiency increases free cholesterol in the livers of Western diet-fed mice or mice with hepatic LDL receptor deficiency, and this effect leads to endoplasmic reticulum stress and release of alanine and aspartate aminotransferases (36,43). Surprisingly, free cholesterol did not accumulate significantly in the intestine of I-Mttp Ϫ/Ϫ mice.…”
Section: Roles Of Intestinal Mtp and Abca1 In Tissue Lipidmentioning
confidence: 99%